Implementasi Kendali Intensitas Cahaya Lampu dengan Internet Of Things Berbasis Arduino Uno menggunakan Metode Fuzzy Logic - Ramdani, Ramdani; Marisa; Carudin, Carudin (LPPM STT Terpadu Nurul Fikri, 2021)
The light intensity setting of the lamp uses the on-off principle for setting the lighting of the lamp. Therefore, the on-off principle base on the dark or lightroom conditions without being affected by the environment. Such conditions result in ineffective and inflexible use of electrical energy. Therefore, changing the light intensity control system from a manual system to an automation system is necessary by implementing the fuzzy logic method as a light intensity controller. The main component of light intensity control using Arduino Uno Microcontroller with data input through AC Light Dimmer sensor and Bluetooth HC-05 is part of the hardware. In contrast, software design uses mobile programming algorithm with APP INVERTOR 2 application and Arduino IDE application. The following weaknesses of the system are made that is how to determine the method of parameter assessment, where the system becomes unstable due to the response to the change of response is very fast and has a small parameter value. This study aimed to create one of the electronic control devices of light intensity control, which the process carried out includes setting the intensity of the lamp freely through a Bluetooth connection of an Android smartphone with the Arduino UNO microcontroller as an electric current regulator on the lamp by the AC Light Dimmer module.